I dropped a big stone on the water snake… Poetic and the Folk Image of a SNAKE - Wołoszyn, Magdalena (Vilnius University Open Series, 2021)
The aim of the article is to reconstruct the linguistic and cultural image of the snake in Polish language and Polish folk culture, functioning within three different but complementary genre-based models: (a) mythological, which echoes are present in belief stories, records of beliefs, and descriptions of practices; (b) biblical (religious), Judeo-Christian, settled in aytiological legends, wedding speeches, religious and historical songs (c) colloquial (common sense), confirmed mainly in colloquial phraseology. In the first model, the snake appears as the guardian of the house and the enclosure, a living creature, friendly to people and animals, whose presence ensures happiness and prosperity; in the second – the serpent is a symbol of evil, sin and Satan; in the third, the most stabilized features of the snake are: wisdom, prudence, but the most of all cunning and sly. The features that emerge especially from the mythological and religious model are the basis for the interpretation of the poetic creation of a snake from Czesław Miłosz’s poem Rue Descartes, in which the lyrical subject combines all evil that has happened to him in his life with in breaking of the ban and just punishment for killing a water snake coiled in the grass.
Keywords: snake; folk linguistic picture of the world; ethnolinguistics; folklore; Czesław Miłosz